Quantification of natural microbial methane from generation to emission in the offshore Aquitaine: A basin modelling approach. (May 2021) - Torelli, Martina; Kowalewski, Isabelle; Gervais, Veronique; Wendebourg, Johannes; Dupré, Stéphanie; Wolf, Sylvie; Gout, Claude; Deville, Eric
Abstract: Marine sediments near continental margins contain sedimentary organic matter (SOM) which is subject to the metabolic activity of micro-organisms during early diagenesis resulting in production of biogenic methane. This process occurs at microscopic scale and anaerobic conditions. Here, we apply a new numerical approach to simulate biogenic methane production offshore Aquitaine (Bay of Biscay) where gas seeps have been recently observed as the result of microbial activity. This new approach accounts for: (1) degradation of a labile-SOM fraction to methane, (2) first order kinetics of the thermal degradation of a thermo-labile-SOM fraction into labile fraction at greater burial and (3) decrease of SOM reactivity with time. First, the organic matter is characterized through pyrolysis using Rock-Eval performed on cuttings collected from two wells located within the methane seepage area. The microbial system is fed from a type III continental-derived SOM which is immature (average Tmax < 425 °C). The basin model is built and calibrated on seismic and well data. It accounts for the consumption of methane required to precipitate methane-derived authigenic carbonates which are found widely distributed on the seafloor as the result of the anaerobic oxidation of methane during upward migration. A sensitivity analysis is performed on the main model input parameters to quantify their impact on the biogenic gas production and expulsion/migration processes. Results led to a reference scenario for microbial gas production in offshore Aquitaine. With this model the generated methane is predominantly dissolved in water and transported by advective processes. Migration is mainly vertical from the source rock layers to the seafloor and controlled by sediment porosity and strata geometry. Modelling can reproduce natural processes such as gas migration at emission points (gas seeps) which have been previously mapped in the offshore Aquitaine Basin. Our results suggest that the biogenic methane is sourced by a present-day active system with a mean flow rate of 27 Mg/y which is relatively lower than flux modelled during the early Pleistocene reaching up to 41 Mg/y. Calculated total methane lost to the seafloor along the Aquitaine Shelf is in accordance with methane flow rate estimated from in situ measurements and acoustic signatures of bubbling sites, and ranges between 0.87 Tcf/My and 1.48 Tcf/My. Here we propose a new workflow to assess and predict biogenic gas occurrences in offshore environment at the basin scale where gas is sourced by recent continental-derived organic matter. This new approach can help to better assess the total biogenic methane budget emitted naturally in the shelf area of oceans that may reach the atmosphere with a negative impact on climate and environment. Highlights: Innovative 3D basin modelling approach to quantify the budget of biogenic methane in continental shelf areas. Sensitivity analysis to determine impact of main parameters on biogenic gas processes in offshore Aquitaine. Quantification of methane consumed as function of efficiency of AOM (Anaerobic Oxidation of Methane). Methane migration is diffuse and mainly vertical from the source rock layers to the seafloor dissolved in pore water. Biogenic methane is sourced by an active system with a maximum flow rate modelled during the early Pleistocene.